Jurnalisme dan Liberalisme: Strategi Susan B. Anthony dalam Merampas Kesetaraan Hak di Amerika Serikat (1868-1900) - Siti Nurmila (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
The status of American women in the early 19th century was not fine. The emergence of gender problems in the United States is one of the protracted problems that took decades, beginning with the inequality between the rights of women and men. This gave rise to a women's movement to get their rights. One of the female figures who participated in the fight for it was Susan B. Anthony. The purpose of this study is to describe the activities of Susan B. Anthony in obtaining equal rights for American women in the aspect of journalism. The method used in this research is the historical or historical method. The steps in this method are heuristics, criticism, and historical writing consisting of historiography, interpretation, explanation and presentation. The results of this study describe the struggle of Susan B. Anthony as a journalist in the feminist movement in the United States, by writing and publishing the newspaper "The Revolution", giving speeches and writing petitions, and writing the book History of Woman Suffrage. Susan B. Anthony's role as both a movement activist and a journalist during the feminist movement in the United States has been an inspiration for American women, especially for the subsequent women's movement activists who continued the feminist movement after Susan B. Anthony retired from the feminist movement activists, until the ratification of the 19th Amendment.